Inovasi Teknologi Pemurnian Minyak Sawit Merah: Studi Integratif dari Penerapan Produksi Bersih dan Optimalisasi Kualitas Minyak dengan Metode Quality Function Deployment (International Forum of Researchers and Lecturers, 2025)
Palm oil is a strategic commodity in the Indonesian economy. Innovation in palm oil filtration is needed to improve the quality and sustainability of production. This article aims to provide insight into the mechanism of the Oil Purification tool based on the Quality Function Deployment (QFD) method and compare it with conventional methods. The method used is a literature review from secondary sources such as journals and scientific articles related to palm oil filtration technology. The results showed that conventional methods have disadvantages such as high oil loss, suboptimal FFA control, and large environmental impacts. In contrast, the Oil Purification tool with QFD and clean production approach offers efficiency, ease of maintenance, and healthier and environmentally friendly filtration results. This innovation is an adaptive and economical solution for small and medium-scale industries.